European Union Law - Horspool, Margot; Humphreys, Mattehew (Oxford Oxford University Press, 2012)
Recoge: 1. Introduction - 2. The constitutional base of the Union - 3. The institutions of the Union - 4. The Union legal system - 5. The European Courts: composition, functions, jurisdiction; preliminary rulings - 6. General principles of law - 7. Direct effect of Union law - 8. Supremacy of Union law - 9. Remedies in Union law - 10. Enforcement of Union law by the institutions - 11. Judicial review of Union action - 12. Citizenship - 13. Free movement of persons: workers and establishment - 14. Free movement of goods (I): the abolition of customs duties and internal taxation - 15. Free movement of goods (II): quantitative restrictions and measures having equivalent effect - 16. Free movement of services: the freedom to provide and receive services - 17. Competition law and policy - 18. Environmental law - 19. Discrimination law: from sex discrimination in employment law to a general equality principle
Keywords: Derecho comunitario